Trends in the Implementation of Higher-Order Thinking Skills in Islamic Religious Education in Madrasahs and Schools: A Systematic Literature Review - Ahmad, Iqbal Faza; Putro, Nur Hidayanto Pancoro Setyo; Thontowi, Zulkifli Syauqi; Syafii, Ahmad; Subakti, M. Aldi (Jurnal Pendidikan Islam, 2020)
The new curriculum (2013 curriculum) encourages implementing the higher-order thinking skills (HOTS) approach in learning Islamic religious education in each academic unit in Indonesia. This paper intends to study the HOTS implementation trend in the learning process of Islamic religious education in Madrasas and schools. The method in this study is a systematic literature review. Researchers found that this trend began to emerge after implementing the 2013 curriculum by the Indonesian Government, where the curriculum used a scientific approach. Teachers, educators, and experts' efforts in implementing HOTS in Islamic Education learning can be grouped into two categories. The first is that they innovate the HOTS-based learning process, and the second is those who develop HOTS-based assessment instruments. Several innovations in the learning process were carried out by applying various learning methods, models, and strategies. The application of HOTS-based learning in Islamic Education learning can improve learning quality to be more effective, efficient, fun, and meaningful. This improvement, then, has an impact on increasing the quality of learning achievement. This study provides highlights and helps to understand the results of previous studies that discuss HOTS using systematic reviews in the implementation of Islamic Religious Education in Madrasas and Schools.